A history of monetary unions - Chown, John F., 1929- (Routledge international studies in money and banking, 2003)
In this comprehensive historical overview, the author writes about Monetary Unions with admirable completeness. Written in a readable and enjoyable prose, A History of Monetary Unions combines historical analysis with present day context.